C In-vivo grafting of large engineered heart tissue patches for cardiac repair. (17th July 2020) - Jabbour, Richard J; Owen, Thomas J; Pandey, Pragati; Reinsch, Marina; Smith, Godfrey; Weinberger, Florian; Eschenhagen, Thomas; Harding, Sian E
Abstract : Introduction: Engineered heart tissue (EHT) strategies, by combining cells within a hydrogel matrix may overcome the limitations of intracoronary/myocardial cell delivery routes. EHTs regenerate heart muscle in small animal models but data regarding clinically relevant engineered heart tissue (EHT) patches large enough for first-in-human studies are lacking. Methods: An upscaled EHT patch (approx. 3 cm × 2 cm × 1.5 mm) consisting of 15–20 million human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CM) embedded in a fibrin based hydrogel was developed. A rabbit myocardial infarction model was then developed to test for feasibility and efficacy of EHT grafting. Results: The patches began to beat spontaneously within 3 days of fabrication and after 28 days of dynamic culture (late EHTs) showed the development of several mature characteristics when compared to early patches (<14 days from fabrication). Late EHTs contained hiPSC-CMs which were more aligned; showed better contraction kinetics, and faster calcium transients. We then tested the EHT patch in-vivo using a rabbit model. Patches were applied to infarcted hearts (n=14 [n=7 EHT vs n=7 sham]). Sham operations used non-cellular fibrin patches. Blinded echocardiographic analysis revealed a significant improvement in function in infarcted hearts that underwent EHT patch grafting (n=7; absolute difference of 10.04 ± 3.1% over sham group; fractional area change, P<0.01). In-vivo telemetry recordings (n=5 MI/sham vs n=7 MI/EHT) indicated that no clinically relevant arrhythmia was seen in the MI/EHT group and arrhythmia provocation protocols (ex vivo n=5 MI/sham vs n=6 MI/EHT) confirmed that the patch was not pro-arrhythmic (arrhythmia inducibility score 5.6 ± 1.0 [MI/patch] vs 5.0 ± 0.6 [MI/sham]; p=ns). Conclusion: An upscaled clinically relevant EHT patch was developed and improved function in infarcted hearts without causing arrhythmia. Therefore EHT may have specific advantages over the direct intramyocardial injection of cells.